Cardiovascular health in breast cancer patients: insight on BRCA1/2 mutations impact - Panagiotis Mallios; Mehdi Dehghan Manshadi; Laila Hubbert; Tajeri Aydin; Claudia Maes; Johanna Rantala; Annelie Liljegren; Narsis A. Kiani; Elham Hedayati (Cardio-Oncology)
Abstract Background Breast cancer (BC) and cardiovascular disease (CVD) are prevalent comorbidities in aging populations. Advances in BC treatment have improved survival rates but increased the risk of CVD, particularly among younger patients with BRCA1/2 mutations. BRCA1/2 gene mutations, prevalent in younger BC patients, impair cardioprotective effects, elevating CVD risk alongside cancer treatments. This study examined the prevalence and incidence of CVD and cardiovascular risk factors (CVRFs) before and after BC diagnosis in BRCA1/2 mutation carriers (BRCA-BC) and those with sporadic BC (Sporadic-BC). Methods This descriptive retrospective cohort study analyzed BC patients from 1995 to 2020 in Stockholm-Gotland, Sweden. Data from regional and national registries provided insights into CVRFs, pre-existing CVDs, demographics, and cancer treatments. Analyses focused on single and multiple CVD events, comparing inpatient and outpatient settings across subgroups. Results The cohort included 438 BRCA-BC and 32,626 Sporadic-BC patients. BRCA-BC patients were younger at BC diagnosis (median: 45 years, IQR 37–53) and first CVD event (median: 62 years, IQR 53–68) compared to Sporadic-BC patients (median: 61 years, IQR 51–71; and 74 years, IQR 65–81, respectively). Before BC diagnosis, CVD prevalence was lower in BRCA-BC patients (4.2%) than in Sporadic-BC patients (11.1%). Post-diagnosis, CVD prevalence increased in both groups, reaching 19.7% in BRCA-BC and 24.6% in Sporadic-BC patients. Heart failure (HF) was the most common major adverse cardiovascular event (MACE), affecting 4.6% of BRCA-BC and 9.5% of Sporadic-BC patients. Sporadic-BC patients exhibited a higher overall cardiovascular burden, including arrhythmias, coronary artery disease, and stroke. Conclusions Distinct cardiovascular profiles between BRCA-BC and Sporadic-BC patients underscore the need for tailored survivorship care. Early cardiovascular screening benefits BRCA-BC patients, while Sporadic-BC patients require comprehensive management of pre-existing CVRFs. These findings align with international cardio-oncology guidelines advocating integrated cardiovascular care for BC survivors.